Male international students' experiences with their professors at a higher education institution in Saudi Arabia: A qualitative study - Albeshir, Saud Ghassan (Journal of Educational and Psychological Sciences, 2025)
This study aimed to explore the experiences of male international students with their lecturers at a Saudi higher education institution, to understand the dimensions of the academic relationship between the two groups, and the extent to which this relationship impacts international students' academic adjustment. The study adopted a qualitative methodology and used interviews to collect data from participants. Thirty-five international students studying at a public university in Saudi Arabia participated in the study. After analyzing the interview results and organizing the data, we divided it into six themes. The results revealed positive overall impressions, as students felt valued and respected, and no cases of discrimination or racism were recorded. The study demonstrated that the instruction methods used were diverse and sensitive to individual differences, relying on technological means to facilitate understanding of the content, especially for students who are not fluent in Arabic. Students also showed a clear tendency to choose professors who are flexible in their assessment and interaction. Despite this progress, the study revealed a lack of consideration for individual differences in assessment, as some students with language difficulties were not given extra time on exams. The results also revealed a high level of academic support outside of class, with professors effectively using their office hours to guide and assist students. Finally, students expressed satisfaction with the level of fairness in treatment and assessment, confirming that they did not feel any discrimination compared to their local colleagues. Concurrently, these results indicate that the educational environment provided to these students is inclusive, supportive, and fair.
Keywords: academic quality; higher education; university professors; international students; total quality